James Harrison Wilson papers - Wilson, James Harrison, 1837-1925.; Wilson, James Harrison, 1837-1925.; Wilson, James Harrison, 1837-1925.; Wilson, James Harrison, 1837-1925.; Wilson, James Harrison, 1837-1925.
Correspondence, journal, speeches, writings, military orders, scrapbook, and other papers relating to the Civil War, railroad affairs, national politics, foreign policy, the Spanish-American War, Cuban affairs, and the China Relief Expedition (1900-1901). Subjects include Civil War campaigns, the postwar Army, the St. Louis and Southeastern Railway Company and railway building in the Mississippi River Valley, life in China in the 1880s and in 1900, Republican Party politics, and the interests of Wilson as a biographer. Includes drafts and typescripts of Wilson's books, Heroes of the Great Conflict; Life and Services of William Farrar Smith (1904), The Life of Charles A. Dana (1907), Under the Old Flag (1912), and The Life of John A. Rawlins (1916). Includes extracts of Rawlins's letters.
Correspondents include Charles Francis Adams, Adam Badeau, Simeon E. Baldwin, Tasker Howard Bliss, Andrew Carnegie, Henry Clark Corbin, E.H. Crowder, Shelby M. Cullom, Charles A. Dana, Grenville Mellen Dodge, Stuyvesant Fish, Hamlin Garland, Frederick John Kingsbury, Robert Todd Lincoln, Henry Cabot Lodge, William McKinley, John Bassett Moore, George Haven Putnam, Whitelaw Reid, Theodore Roosevelt, Elihu Root, Francis Lynde Stetson, Moorfield Storey, Oswald Garrison Villard, Paul M. Warburg, Horace White, Edward Francis Winslow, and John Russell Young.
Soldier, railroad builder, and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, Charles Francis, -- 1835-1915 -- Correspondence; Badeau, Adam, -- 1831-1895 -- Correspondence; Baldwin, Simeon E. -- 1840-1927 -- Correspondence; Bliss, Tasker Howard, -- 1853-1930 -- Correspondence; Carnegie, Andrew, -- 1835-1919 -- Correspondence; Corbin, Henry Clark, -- 1842-1909 -- Correspondence; Crowder, E. H. -- 1859-1932 -- Correspondence; Cullom, Shelby M. -- 1829-1914 -- Correspondence; Dana, Charles A. -- 1819-1897.; Dana, Charles A. -- 1819-1897 -- Correspondence; Dodge, Grenville Mellen, -- 1831-1916 -- Correspondence; Fish, Stuyvesant, -- 1851-1923 -- Correspondence; Garland, Hamlin, -- 1860-1940 -- Correspondence; Kingsbury, Frederick John, -- 1823-1910 -- Correspondence; Lincoln, Robert Todd, -- 1843-1926 -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; McKinley, William, -- 1843-1901 -- Correspondence; Moore, John Bassett, -- 1860-1947 -- Correspondence; Putnam, George Haven, -- 1844-1930 -- Correspondence; Rawlins, John A. -- 1831-1869.; Rawlins, John A. -- 1831-1869 -- Correspondence; Reid, Whitelaw, -- 1837-1912 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Smith, William Farrar, -- 1824-1903.; Stetson, Francis Lynde -- Correspondence; Storey, Moorfield, -- 1845-1929 -- Correspondence; Villard, Oswald Garrison, -- 1872-1949 -- Correspondence; Warburg, Paul M. -- 1868-1932 -- Correspondence; White, Horace, -- 1834-1916 -- Correspondence; Winslow, Edward Francis, -- 1837-1914 -- Correspondence; Young, John Russell, -- 1840-1899 -- Correspondence; United States. -- Army; Republican Party (U.S. : 1854- ); St. Louis and Southeastern Railway Company; International relief -- China; Railroads -- Mississippi River Valley; Railroads -- United States; Spanish-American War, 1898.; China -- Social conditions -- 1644-1912.; Cuba -- History -- 1895-; United States -- Foreign relations -- 1865-1921.; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- Politics and government -- 1865-1933.; Authors; Railroad builders; Soldiers